Implementasi Pendekatan Pembelajaran Aktif (Active Learning) dalam Program Bimbingan Calistung bagi Anak Usia Dini di Desa Tibang - Risma, Nadila (Jurnal Riset dan Pengabdian Masyarakat, 2026)
The Active Learning–based literacy program was implemented for early childhood learners up to third-grade students in Tibang Village to improve their reading, writing, and numeracy skills. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results show that Active Learning effectively increases children’s engagement, learning motivation, and gradual improvement in basic literacy skills through play-based activities, concrete learning media, and guided practice. This program proves to be an effective non-formal learning model to strengthen foundational literacy from an early age.